Corporate Reporting on the Internet by Pusat Kutipan Zakat - Nikmal Muzal, Mohd Muhaiyuddin (2011)
The Internet has emerged as the preferred communication platform for the dissemination of information among corporate companies. The existence of the company's website has become an important medium for corporate purposes. In view of financial reporting through the internet are voluntary, many studies have been conducted to explain the practice. This study however, focuses particularly on the practices of the institutions of zakat that is an important Islamic institutions in Malaysia. The objectives of this study are to identify the financial reporting practices by institutions of zakat and to identify type of information reported by institutions of zakat through the internet. To accomplish these objectives, an adapted list contains a series of comprehensive criteria was applied to all zakat institutions in Malaysia specifically to examine disclosure of information on the web. Result revealed that all the all fourteen zakat institutions in Malaysia have their webpage available except for Johor which is still under construction. However, the type of information reported by these institution are still limited with many are only reporting on current zakat collection and distribution only.